2004
DOI: 10.1080/00015458.2004.11679617
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Bilateral Spontaneous Pneumothorax Report of 12 Cases and Review of the Literature

Abstract: Simultaneous bilateral spontaneous pneumothorax (SBSP) is a very rare condition, mainly seen in patients with underlying lung disease. Up to now, there are 65 patients who have been published. Twelve consecutive patients who presented with SBSP as definitive diagnosis were recruited for this study. They represented 1 % of all patients with spontaneous pneumothorax. All patients had immediate bilateral chest tubes on admission. Five of the 12 patients (42%) had no underlying lung disease. In 7 patients, SBSP wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
80
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 30 publications
1
80
1
3
Order By: Relevance
“…The prevalence of PAL (14.9%) and ipsilateral recurrence (14.4%) in our study was similar to those reported in the literature. 11,14) As the recurrence rates have been reported to be 54% within four years after the first attack, it can be thought that the recurrence rate in our study might be increased after long follow-up period. 15) Bulla/bleb resection and wide pleural abrasion was applied to our patients via AT or VATS.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The prevalence of PAL (14.9%) and ipsilateral recurrence (14.4%) in our study was similar to those reported in the literature. 11,14) As the recurrence rates have been reported to be 54% within four years after the first attack, it can be thought that the recurrence rate in our study might be increased after long follow-up period. 15) Bulla/bleb resection and wide pleural abrasion was applied to our patients via AT or VATS.…”
Section: Discussionmentioning
confidence: 54%
“…Surgical therapy is also recommended in patients with pneumonectomy, in pilots or divers in the first pneumothorax attack and in patients with bilateral synchronous pneumothorax. 3,4,11) Surgical methods include wedge resection and pleurectomy/pleural abrasion with VATS or AT and simple thoracoscopic talcage. However, the time for surgery, how many days should be considered as the limit for PAL, and after how many ipsilateral recurrences operation is required are still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…[1] The common associations include sarcomas of various origins, histiocytosis X, lymphomas, primary and metastatic lung malignancies, interstitial lung diseases, and infections. [2] Our patient had scrub typhus infection with pulmonary complications like interstitial pneumonitis with acute respiratory distresssyndrome (ARDS) and simultaneous bilateral spontaneous pneumothorax (SBSP). Scrub typhus is widespread across the world, extending from Japan to Australia and from India to Pacific.…”
Section: Discussionmentioning
confidence: 99%
“…The operation time was shortened in this way. Bilateral spontaneous pneumothorax could result from sarcoidosis, lymphangioleiomyomatosis, Marfan's syndrome, metastasis, tuberculosis, and mesothelioma (5)(6)(7)(8). For this reason, systemic physical examination should be conducted on these patients.…”
Section: Discussionmentioning
confidence: 99%